PENERAPAN MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VI C PADA MATERI UNSUR INTRINSIK CERPEN DI SD NEGERI BONTOKAMASE: Penelitian Tindakan Kelas - Riska Amalia; Windy Irianti Putri (STKIP Subang, 2024)
Pre-test results of class VI C students at SD Negeri Bontokamase regarding the intrinsic elements of short stories indicated that many students still had results below the KKM. This study aims to improve student's learning outcomes on the material of intrinsic elements of short stories by using the Teams Games Tournament (TGT) learning model. The object of this research is class VI C students of SD Negeri Bontokamase, totaling 35 students. The learning test results obtained increased with a classical completeness of 74.28%. Based on the result, it can be concluded that implementing the Teams Games Tournament (TGT) learning model can increase students' learning outcomes on the material of the intrinsic elements of short stories.